2020
DOI: 10.1177/1049732320960417
|View full text |Cite
|
Sign up to set email alerts
|

“Our Beauty Is in Our Breasts”: A Culture-Centered Approach to Understanding Cancer Perceptions in Kwa Zulu Natal, South Africa

Abstract: Breast cancer is an incapacitating physical illness. It was once reported predominantly by patients in developed countries. With the advent of globalization, it is increasingly becoming a major health concern in developing countries such as South Africa. Breast cancer researchers have continuously advocated for original studies that address this condition from a sociocultural perspective. Consequently, in this article I examine the perceptions of breast cancer patients from underprivileged parts of Kwa Zulu Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…In total, 48 studies were included, comprising quantitative (n = 24), qualitative (n = 23) and mixed methods 75 (n = 4) 33,35,41,50 ), (qualitative studies (n = 8) [53][54][55][56]58,60,66,71 ); Ghana (n = 11) (quantitative studies (n = 6) 31,32,36,39,48,51 ), (qualitative studies (n = 5) 57,61,63,69,72 ); Mali (n = 1) (quantitative studies (n = 1) 29 )); Central or Middle Africa (Cameroon (n = 1) (quantitative studies (n = 1) 28 )), Southern Africa (South Africa (n = 9) (quantitative studies (n = 1) 34 ), (qualitative studies (n = 8) 59,62,64,65,67,68,70,73 )), East Africa (Ethiopia (n = 9) (quantitative studies (n = 7) 30,37,40,42,44,46,47 ) (qualitative studies (n = 1) 74 ) (mixed method studies (n = 1) 75 );…”
Section: Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 48 studies were included, comprising quantitative (n = 24), qualitative (n = 23) and mixed methods 75 (n = 4) 33,35,41,50 ), (qualitative studies (n = 8) [53][54][55][56]58,60,66,71 ); Ghana (n = 11) (quantitative studies (n = 6) 31,32,36,39,48,51 ), (qualitative studies (n = 5) 57,61,63,69,72 ); Mali (n = 1) (quantitative studies (n = 1) 29 )); Central or Middle Africa (Cameroon (n = 1) (quantitative studies (n = 1) 28 )), Southern Africa (South Africa (n = 9) (quantitative studies (n = 1) 34 ), (qualitative studies (n = 8) 59,62,64,65,67,68,70,73 )), East Africa (Ethiopia (n = 9) (quantitative studies (n = 7) 30,37,40,42,44,46,47 ) (qualitative studies (n = 1) 74 ) (mixed method studies (n = 1) 75 );…”
Section: Searchmentioning
confidence: 99%
“…58,60,65,75 In a study conducted in Ethiopia, breast cancer was reported to potentially be caused by mich (an Ethiopian ethnomedical category roughly equivalent to 'bad air'). 75 Studies commonly reported experiencing health service-related barriers to appropriate care (e.g., health professionals misdiagnosing their breast cancer, even after multiple attendances at health facilities 52,[54][55][56][59][60][61]63,64 ). Additional barriers contributing to delays in accessing care included language barriers where English was not a first language and the need for translators to communicate with health professionals.…”
Section: Adversity: Realising Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Portanto, possibilita uma exacerbação enfermidade, e assim dos estigmas, principalmente quando esta enfermidade tem como ação a mastectomia, que tem como consequência o medo a culpa (Zwane, 2021, Fonseca et al, 2020.…”
Section: Introductionunclassified